Synchrotron Radiation X-Ray Absorption Spectroscopy and Spectroscopic Ellipsometry Studies of InSb Thin Films on GaAs Grown by Metalorganic Chemical Vapor Deposition. (8th July 2018) - Qian, Yingda; Liang, Yuanlan; Luo, Xuguang; He, Kaiyan; Sun, Wenhong; Lin, Hao-Hsiung; Talwar, Devki N.; Chan, Ting-Shan; Ferguson, Ian; Wan, Lingyu; Yang, Qingyi; Feng, Zhe Chuan
Abstract : A series of ultrathin InSb films grown on GaAs by low-pressure metalorganic chemical vapor deposition with different V/III ratios were investigated thoroughly using spectroscopic ellipsometry (SE), X-ray diffraction, and synchrotron radiation X-ray absorption spectroscopy. The results predicted that InSb films on GaAs grown under too high or too low V/III ratios are with poor quality, while those grown with proper V/III ratios of 4.20–4.78 possess the high crystalline quality. The temperature-dependent SE (20–300°C) and simulation showed smooth variations of SE spectra, optical constants ( n, k, e 1, and ε 2 ), and critical energy points (E 1, E 1 + Δ 1, E ′ 0, E 2, and E ′ 1 ) for InSb film when temperature increased from 20°C to 250°C, while at 300°C, large changes appeared. Our study revealed the oxidation of about two atomic layers and the formation of an indium-oxide (InO) layer of ∼5.4 nm. This indicates the high temperature limitation for the use of InSb/GaAs materials, up to 250°C.